Filariasis research – from basic research to drug development and novel diagnostics, over a decade of research at the Institute for Medical Microbiology, Immunology and Parasitology, Bonn, Germany - Karunakaran, Indulekha; Ritter, Manuel; Pfarr, Kenneth; Klarmann-Schulz, Ute; Debrah, Alexander Yaw; Debrah, Linda Batsa; Katawa, Gnatoulma; Wanji, Samuel; Specht, Sabine; Adjobimey, Tomabu; Hübner, Marc Peter; Hoerauf, Achim (Frontiers in Tropical Diseases, 2023)
Filariae are vector borne parasitic nematodes, endemic in tropical and subtropical regions causing avoidable infections ranging from asymptomatic to stigmatizing and disfiguring disease. The filarial species that are the major focus of our institution’s research are Onchocerca volvulus causing onchocerciasis (river blindness), Wuchereria bancrofti and Brugia spp. causing lymphatic filariasis (elephantiasis), Loa loa causing loiasis (African eye worm), and Mansonella spp causing mansonellosis. This paper aims to showcase the contribution of our institution and our collaborating partners to filarial research and covers decades of long research spanning basic research using the Litomosoides sigmodontis animal model to development of drugs and novel diagnostics. Research with the L. sigmodontis model has been extensively useful in elucidating protective immune responses against filariae as well as in identifying the mechanisms of filarial immunomodulation during metabolic, autoimmune and infectious diseases. The institute for Medical Microbiology, Immunology and Parasitology (IMMIP), University Hospital Bonn (UKB), Bonn, Germany has also been actively involved in translational research in contributing to the identification of new drug targets and pre-clinical drug research with successful and ongoing partnership with sub-Saharan Africa, mainly Ghana (the Kumasi Centre for Collaborative Research (KCCR)), Cameroon (University of Buea (UB)) and Togo (Laboratoire de Microbiologie et de Contrôle de Qualité des Denrées Alimentaires (LAMICODA)), Asia and industry partners. Further, in the direction of developing novel diagnostics that are sensitive, time, and labour saving, we have developed sensitive qPCRs as well as LAMP assays and are currently working on artificial intelligence based histology analysis for onchocerciasis. The article also highlights our ongoing research and the need for novel animal models and new drug targets.